PERBEDAAN PRESTASI BELAJAR FISIKA ANTARA PESERTA DIDIK YANG DIAJAR DENGAN METODE LEVELS OF INQUIRY LEARNING CYCLE DAN METODE CERAMAH - Triwijayanti, Nobita; Loekmono, J.T. Lobby; Sutriyono, Sutriyono (Universitas Kristen Satya Wacana, 2015)
Type of this research is experiment research which has a purpose to know the diffrence of phisics study achievement among students taught with levels of inquiry learning cycle method and students taught with direct teaching method. The participants were 46 students from XI SMK official school, Landak District, West Kalimantan. The data were taken by using t test and the result shows there is significant difference between students taught with levels of inquiry learning cycle method and students taught with direct teaching method. The students score average of inquiry learning cycle method is better than the students score of direct teaching method.